Foreign-Capital Utilization and Economic Policies in Developing Countries In Developing Countries - Areskoug, Kaj (The Review of Economics and Statistics, 1973)
T HE traditional aid-and-development literature assumes that, under most relevant circumstances, aid and other capital flows to developing countries induce an expansion of economic activity and output in these countries. In the underlying models such capital finances an equivalent amount of net imports of either (a) capital goods of an unspecified nature (thereby relaxing the saving constraint) or (b) specific required inputs obtainable only from abroad (thereby relaxing the foreign-exchange constraint).' A number of writers have estimated the effects of past capital inflows and capital requirements on the basis of 'this assumption, without seriously questioning its validity (Rosenstein-Rodan 1961; Chenery and Bruno 1962; Manne 1963). Several recent writers, however, have criticized this view, both because of its formal incompatibility with other aspects of the theoretical models employed and because of its inconsistency with empirical observation (Rahman 1968, Areskoug 1969, Chenery and Eckstein 1970, Griffin 1970, Griffin and Enos 1970, Weisskopf 1972).2 It seems that a considerable portion of these capital inflows have in fact been allocated to consumption and that ties and other creditor (donor) restrictions designed to channel them into investment have been largely ineffective. The traditional aid-and-development models must therefore be deficient.